Are acute:chronic workload ratios of perceived exertion and running based variables sensible to detect variations between player positions over the season? A soccer team study - Nobari, H.; Arslan, E.; Martins, A. D.; Oliveira, R. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background The aim of this study was to describe and compare the in-season variations of acute: chronic workload ratio (ACWR) coupled, uncoupled, and exponentially weighted moving average (EWMA) through session rating of perceived exertion (s-RPE), total distance (TD), high-speed running distance (HSRD) and sprint distance (SPRINT) in three different periods of an elite soccer season according to player positions.